The Application of Digital Marketing Through Whatsapp Marketing in an Effort to Increase Sales of Sewing Service MSMEs in Kupang City - Sultan, Taqwa; K, Margaretha Sartien (International Journal on Social Science, Economics and Art, 2024)
The development of increasingly technology is inevitable in human life, so that currently people are brought to the phenomenon of social commerce (s-commerce), which is a situation where social media is also used as a means of buying and selling transactions. One of the uses of digital media is digital marketing activities, where traders promote and market their products online. The purpose of this study is to find out how the marketing strategy uses Whatsapp Marketing for UMKM Sewing Services in Kupang City. This study uses a descriptive qualitative method and is carried out data reduction data analysis techniques, data presentation, and conclusion drawn. The result of this study is that there are 4 strategies used by UMKM in Sewing Services in marketing efforts to increase sales volume. By using the features in WhatsApp Business, such as: 1) Auto Reply, 2) Product Catalog, 3) Message Labels, and 4) Message Statistics.